2016
DOI: 10.1371/journal.pone.0149643
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Relationship with Anxiety in University Students: A Cross-Sectional Designed Study

Abstract: PurposeSleep disorders (SDs) are now recognized as a public health concern with considerable psychiatric and societal consequences specifically on the academic life of students. The aims of this study were to assess SDs in a group of university students in Lebanon and to examine the relationship between SDs and anxiety.MethodsAn observational cross-sectional study was conducted at Saint-Joseph University, Lebanon, during the academic year 2013–2014. Four questionnaires were face-to-face administered to 462 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 41 publications
9
76
2
12
Order By: Relevance
“…The present study revealed the current statuses of university students with regard to insomnia, insufficient sleep, and delayed sleep-wake phase. In a previous systematic review on insomnia in university students, the prevalence of insomnia ranged from 9.4 to 38.2% [35][36][37]. The prevalence of insomnia among the university students included in the present study fell within this range.…”
Section: Insomnia Insufficient Sleep and Delayed Sleep-wake Phase Insupporting
confidence: 46%
“…The present study revealed the current statuses of university students with regard to insomnia, insufficient sleep, and delayed sleep-wake phase. In a previous systematic review on insomnia in university students, the prevalence of insomnia ranged from 9.4 to 38.2% [35][36][37]. The prevalence of insomnia among the university students included in the present study fell within this range.…”
Section: Insomnia Insufficient Sleep and Delayed Sleep-wake Phase Insupporting
confidence: 46%
“…Greater sleep debt has been shown to explain the relationship between eveningness and depressive symptoms in university students (Bakotic, Radosevic‐Vidacek, & Koscec Bjelajac, ). Additionally, up to 50% of university students report daytime sleepiness (Lund et al., ; Oginska & Pokorski, ), which associates with increased risk of depression (Nyer et al., ; Regestein et al., ) and anxiety among students (Choueiry et al., ). Compared to other chronotypes, young adult evening‐types at university also report greater daytime sleepiness (Fernández‐Mendoza et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia has numerous associated complications such as; poor sleep quality, anxiety, depression 16,17 , and even affect memory and performance during the day, thus modifying student performance in university life 18 . ANOVA test and post hoc Bonferroni, adjusted for sex, consume tobacco; Odds Ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders have increased over the last few years. University students, because they are constantly confronted with a condition of maintained stress, affect the quality of sleep in general, thus increasing anxiety which in turn is significantly associated with daytime sleepiness and insomnia 17 .…”
Section: Sleep Disorders and Anthropometric Measures In Chilean Univementioning
confidence: 99%